2010
DOI: 10.1073/pnas.1008133107
|View full text |Cite
|
Sign up to set email alerts
|

GAPDH regulates cellular heme insertion into inducible nitric oxide synthase

Abstract: Heme proteins play essential roles in biology, but little is known about heme transport inside mammalian cells or how heme is inserted into soluble proteins. We recently found that nitric oxide (NO) blocks cells from inserting heme into several proteins, including cytochrome P450s, hemoglobin, NO synthases, and catalase. This finding led us to explore the basis for NO inhibition and to identify cytosolic proteins that may be involved, using inducible NO synthase (iNOS) as a model target. Surprisingly, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 37 publications
6
154
0
1
Order By: Relevance
“…Our findings that GAPDH and NO regulate heme availability and mobilization are highly reminiscent of and supported by previous studies demonstrating that GAPDH and NO cooperate to control heme insertion into nitric oxide synthase (32). As such, it is tempting to speculate that Tdh3p is the source of NO-mobilized heme.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings that GAPDH and NO regulate heme availability and mobilization are highly reminiscent of and supported by previous studies demonstrating that GAPDH and NO cooperate to control heme insertion into nitric oxide synthase (32). As such, it is tempting to speculate that Tdh3p is the source of NO-mobilized heme.…”
Section: Discussionsupporting
confidence: 89%
“…Given the HS1-M7A K d II of 25 nM, we estimate that heme is buffered at an upper limit of 2.5 nM in the mitochondria and nucleus. This concentration corresponds to fewer than six molecules in the nucleus [V nuc ∼ 5 fL (30) (32). Could NO also mobilize LH pools?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAPDH is known to be an enzyme catalyzing the conversion of glyceraldehyde-3-phosphate into 1,3-bisphosphoglycerate. Chakravarti et al [76] found that GAPDH interacts with both heme and iNOS. Knockdown of GAPDH or mutation of the heme-binding site in GAPDH significantly reduced heme incorporation into iNOS.…”
Section: Intracellular Heme Transportmentioning
confidence: 99%
“…Knockdown of GAPDH or mutation of the heme-binding site in GAPDH significantly reduced heme incorporation into iNOS. The product of iNOS, nitric oxide (NO), also inhibited heme insertion into iNOS through S-nitrosylation of GAPDH [76]. Heme insertion into sGC was found to be mediated by HSP90, which preferentially interacts with apo-sGC [77].…”
Section: Intracellular Heme Transportmentioning
confidence: 99%